2020
DOI: 10.1200/jco.19.02381
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Patient-Reported Outcomes With Intensity-Modulated Radiotherapy (RT) Compared With Standard RT: A Report From the NRG Oncology RTOG 1203 Study

Abstract: PURPOSE In oncology trials, the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) is the standard tool for reporting adverse events (AEs), but it may underreport symptoms experienced by patients. This analysis of the NRG Oncology RTOG 1203 compared symptom reporting by patients and clinicians during radiotherapy (RT). PATIENTS AND METHODS Patients with cervical or endometrial cancer requiring postoperative RT were randomly assigned to standard 4-field RT or intensity-modulated RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 18 publications
2
75
0
1
Order By: Relevance
“…Previous studies have found that hematologic toxicity varies as a function of bone marrow radiation dose, volume, and location ( 5 , 10 , 13 , 17 23 ). These studies have led to the development of bone marrow radiation dose constraints that have been incorporated into clinical trials and routine practice for cervical cancer patients ( 5 , 6 ). It is not known whether additional reduction in marrow radiation, on par with levels in head/neck cancer treatment, would further reduce toxicity or whether benefits would outweigh risks associated with potentially increased dose to other organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that hematologic toxicity varies as a function of bone marrow radiation dose, volume, and location ( 5 , 10 , 13 , 17 23 ). These studies have led to the development of bone marrow radiation dose constraints that have been incorporated into clinical trials and routine practice for cervical cancer patients ( 5 , 6 ). It is not known whether additional reduction in marrow radiation, on par with levels in head/neck cancer treatment, would further reduce toxicity or whether benefits would outweigh risks associated with potentially increased dose to other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution in radiation technology has allowed substantially greater ability to reduce dose to critical normal tissues, such as bone marrow, offering the possibility to preserve hematopoietic function and permit better treatment tolerance in patients undergoing chemoradiotherapy. Bone marrow dose constraints have been integrated into clinical trials and routine practice for cervical cancer patients ( 5 , 6 ). However, it is unclear whether greater reductions in bone marrow doses, such as can be achieved with proton therapy ( 7 ), would further limit hematopoietic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, this trial primarily investigates impact on quality of life endpoints associated with hypofractionated WPRT through a non-inferiority study design and by using a validated patient-reported outcome questionnaire. These questionnaires are known to better represent symptomatic adverse reactions experienced by patients receiving WPRT when compared to physician-reported endpoints [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain reliable information about toxicities that influence patient's quality of life, normal tissue toxicities are likely best represented by patient-reported outcomes (PROs) ( 7 ). Using clinical decision-support tools ( 8 , 9 ) and keeping the number of items/questions as few as possible ( 10 ) are necessary for actionability to patient-reported complaints.…”
Section: Literature Resources For Outcome Modeling In Radiotherapymentioning
confidence: 99%